Factors affecting Mycoparasitism of Sclerotinia Sclerotiorum by Trichoderma spp. - DINESH SINGH; PRATIBHA SHARMA, GOPI KISHAN*, RAHUL TIWARI, G. PRAKASH (Indian Phytopathology, 2017)
Studies were conducted to investigate different factors favoring mycoparasitism of Sclerotinia sclerotiorum by Trichoderma spp. Results indicate that both temperature and pH have a significant effect on mycoparasitism. Trichoderma viride at 15°C and T. harzianum (Th3) at 25°C were most effective in inhibiting upto 86.90% and 78.96 % mycelial growth, respectively. The pathogen growth was not observed in most of the dual culture plates as well as in control at 35°C. At different pH, Trichoderma behaved differently as it was less effective at pH 9 as compared to pH 5 and 7. At pH 5 Th3 inhibited up to 92 per cent growth of some of the isolates of S. sclerotiorum while at pH 7 it inhibited up to 79 per cent of growth of pathogen. At combination of different temperature and pH, Th3 inhibited up to 81, 73 and 60 per cent growth at pH 5, 7 and 9 at 15°C respectively. At 25°C Th3 inhibited 86, 82 and 55 per cent growth of pathogen at pH 5, 7 and 9 respectively. Th3 had a very effective biocontrol potential at temperature 15°C, 25°C and pH 5 and 7. At pH 9 it was able to inhibit the mycelial growth of pathogen up to 55 per cent.